Pengaruh Penggunaan Aplikasi Kahoot Terhadap Motivasi Belajar Bahasa Arab Siswa Kelas X MAN 4 Kebumen - Aulia Karima Zuhda Utami; Dudung Hamdun (Edulab : Majalah Ilmiah Laboratorium Pendidikan, 2020)
This study aims to determine the difference between the motivation of learning Arabic experimental class (which uses the kahoot application) and the control class (not using the kahoot application) in class X MAN 4 Kebumen. This research is a quasi experimental research. The research sample was taken by purposive sampling technique and class X IPA 1 was taken as a control group and class X IPA 2 as an experimental group. Data collection is done by using a questionnaire, observation and documentation. The instrument validity test was performed using the product moment correlation formula. Reliability test using the Cronbach Alpha formula. Data analysis was performed with prerequisite test analysis and hypothesis testing. The results showed that there were significant differences between the motivation of learning Arabic in the control class and the experimental class. This is indicated by the significance value in the t test of 0.018 <0.05. The average post-test of the experimental class is higher than the average of the post-test of the control class (98,735> 92,363). Keywords: Kahoot Application, Motivation, Arabic Learning